An Intervention On Surya Namaskar; A Pilot Study - Changmai, Satya; Kumar Singh, Vivek; Chikro, Yuhey; Moniya, Tage; Talung, Gollo; Suhindar Singh, Nongmaithem (Cuestiones de Fisioterapia, 2025)
Objective of the study is to find out the effect of repetitions of one-minute surya namaskar for twoweeks on selected variables viz; Vo2 Max, Strength Endurance and Flexibility.Procedure and Methodology: Thirty male subjects (students) age ranging from 14 to 17 students wererandomly selected for the purpose of the study. Vo2 Max, Strength Endurance and Flexibility were selected asthe dependent variable. The pre-test and post-test randomized group design was used. The subjects wererandomly divided into two groups i.e. experimental (15 nos) and control group (15 nos). Experimental groupwere given Yoga Intervention of one minute pace of surya namaskar for three weeks (for three times a week)and control group as continuing regular activities. All the subjects were tested prior and after three weeks ofsurya namaskar training with one minute on selected variables viz., Vo2 Max, Strength Endurance andFlexibility. The descriptive statistics such as mean, median, mode, standard deviation, maximum and minimumwas used and to find out the significant difference of the means between experimental group and control group